UC3 Model for Primary Grades Problem Solving - Rachel Joy M. Carriaga-Baril (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to determine the effectiveness of Polya’s UC3 model in improving the problem-solving skills and attitude and perception towards problem-solving of grade 2 students. Quantitative data were gathered through a two-group pre-posttest quasi-experimental design, and qualitative data were gathered through focused group discussion from 54 grade two students through convenient sampling. The Paired T-test and T-test for independent samples results revealed that UC3 model has increased students’ problem-solving skills to Satisfactory level with a significant pair difference and mean gain as compared to conventional method. It has also increased students’ attitude and perception with a significant mean gain in growth mindset and interest. Based on the findings, it is concluded that the utilization of the UC3 Model in teaching problem solving is effective in improving students’ skills and attitude and perception towards problem solving of grade 2 students. It further recommends for provision of programs and workshops by administrations, integration of UC3 in classroom instruction by the teachers, and further validation of findings by other researchers.